Analisis Pendapatan Istri Nelayan dalam Upaya Meningkatkan Pendapatan Keluarga - Puspita, Luh Made Ratna; Widanta, A.A. Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 7, Juli 2016 (pp. 729-947), 2016)
This study aimed to analyze the influence of the woman's age, level of education, length of service and training partially and simultaneously on revenue fisherman's wife with efforts increasing family income in Village Attack. The population in this study was the wife of a fisherman in the village attack. Sample method using saturated sample. The total sample used as many as 80 people. Data analysis using multiple linear regression analysis. Based on the analysis of the research found that simultaneous variables age, level of education, working hours and training and a positive effect on the income sinifikan fisherman's wife in the village of Serangan by 63.5 percent. Partially age, level of education, working hours and training positive and significant impact on the income of fishermen in the village of Serangan wife.
Keywords: Age, level of education, time employment, training, income of fisherman' s wife